Etiological and Clinical Profile of Acute Nonbacterial Encephalitis in Children: A Single-Center Prospective Study - Cengiz, Ali Bülent; Günbey, Ceren; Ceyhan, Mehmet; Korukluoğlu, Gülay; Tanır Başaranoğlu, Sevgen; Eroğlu Ertuğrul, Nesibe Gevher; Coşgun, Yasemin; Konuşkan, Bahadır; Özsürekci, Yasemin; Anlar, Banu (Neuropediatrics, 2021)
Encephalitis is a serious neurological syndrome caused by inflammation of the brain. The diagnosis can be challenging and etiology remains unidentified in about half of the pediatric cases. We aimed to investigate demographic, clinical, laboratory, electroencephalographic and neuroimaging findings, and outcome of acute encephalitis of nonbacterial etiology. This prospective study included children hospitalized with the diagnosis of acute encephalitis between 2017 and 2019. Microbiological investigations of the cerebrospinal fluid (CSF) were recorded. All CSF specimens were tested for anti-N methyl D-aspartate receptor (NMDAR) antibodies. In total, 31 children aged 10 months to 17 years (median = 6 years) were included. Pathogens were confirmed in CSF in three patients (9.7%): varicella zoster virus, herpes simplex virus type 1 (HSV-1), and both HSV-1 and NMDAR antibodies. Presenting features included encephalopathy (100%), fever (80.6%), seizure (45.2%), focal neurological signs (29%), and ataxia (19.4%). On clinical follow-up of median 9 (6–24) months, six patients showed neurological deficits: together with two patients who died in hospital, total eight (25.8%) patients were considered to have unfavorable outcome. Need for intubation, receiving immunomodulatory treatment, prolonged hospitalization, and high erythrocyte sedimentation rate at admission were associated with unfavorable outcome. The etiology of encephalitis remains unexplained in the majority of children. HSV-1 is the most frequently detected virus, consistent with the literature. The fact that anti-NMDAR encephalitis was detected in one child suggests autoimmune encephalitis not being rare in our center. The outcome is favorable in the majority while about one-fifth of cases suffer from sequelae.
Keywords: encephalitis; children; virus; anti-NMDA receptor antibodies